Everybody lies : big data, new data, and what the Internet can tell us about who we really are - Stephens-Davidowitz, Seth (Dey St., an imprint of William Morrow, 2017)
A former Google data scientist presents an insider's look at what the vast, instantly available amounts of information from the Internet can reveal about human civilization and society.